Integrated Pest Management in Protected Structures I: Basic Principles and Scouting - Hugh A. Smith; Gary E. Vallad; Bielinski M. Santos (EDIS)
The fundamentals of managing pests in protected structures are very similar in many respects to managing pests in field crops. But conditions within a protected structure can be modified to a certain degree to prevent, delay, or even mitigate pest issues. On the other hand, conditions that discourage one group of pests can often favor another. This 7-page fact sheet was written by Hugh A. Smith, Gary E. Vallad, and Bielinski M. Santos, and published by the UF Department of Entomology and Nematology, June 2013.